PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP RENTABILITAS EKONOMI - Supriadi, H.; Sapta, W.P; Aslichah, Hj. (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2018)
This study aims to identify and analyze the influence of cash turnover and accounts receivable turnover simultaneously, identify and analyze the effect of cash turnover and accounts receivable turnover of the economic profitability partially, and determine the dominant factor affecting the economic profitability. This research was conducted in cooperation with the reason that the Cooperative is a service company and trade. This research was conducted quantitative descriptive approach. The data collection is done by means of documentation and interviews were unstructured. The data used are secondary data derived from study subjects. The analytical method used is multiple linear regression with Ordinary Least Square method. The findings of this study include are:  a significant difference between cash turnover and accounts receivable turnover of the economic profitability simultaneously. a significant difference between the cash turnover receivables turnover against economic profitability partially. Receivables turnover is a dominant factor affecting the economic profitability.